Frequency and distribution of risk factors for coronary heart disease in the adult population of rural district of Elazığ, Turkey - Açık, Yasemin; Sezer, Erol; Sezer, Hafize (My University, 1999)
Objectives: This study was performed to determine the frequency and distribution of risk factors for coronary heart disease in people living in the Baskil district of Elazığ. Methods: From a population of 905 individuals aged 35 years and over, 388 were randomly selected. Selection of subjects was done with official records of the Baskil Health Care Center. Although repeated invitations were made, 32 individuals (29 men and 3 women) did not participate. Thus, 356 subjects were enrolled. Blood cholesterol and blood pressure levels, body height and weight were measured in all study subjects. In addition, a questionnaire was applied. Results: Mean cholesterol levels were found to be 195.8 mg/dL and 197.5 mg/dL in men and women, respectively. Cholesterol levels of men and women were above 240 mg/dL in 9.3% and 17.5% of men and women, respectively. The prevalence of cigarette smoking was higher in men (58.7%) than in women (13.1%). The prevalence of hypertension (systolic blood pressure >140 mmHg and /or diastolic blood pressure >90 mmHg) was found to be 51.9%, being 51.3% in men and 52.4% in women. Prevalence of obesity according to the body mass index criteria (over 30 kg/m2) was 12% in men and 31.6% in women (p=0.0001). Only 9.3% of men and 2.4% of women reported participating in regular physical activity (p<0.005). Animal fat and products were the leading sources of dietary fat intake (46.6%), followed by vegetable oils (28.7%), and margarine (24.7%). Based on the subjects' accounts, the prevalence of diabetes mellitus was 5.6%, being 2.7% in men and 7.7% in women. Conclusions: This study indicated that the prevalence of major risk factors for coronary heart disease was high in people living in rural areas of Elazığ. As there are few population-based studies performed on the prevalence of risk factors for coronary heart disease, this study may be of value in reflecting the situation in rural areas of Turkey.
Keywords: Turkey; Coronary Disease; Risk Factors; Adult; Adult population; Coronary heart disease